Financial Sector Assessment : Poland - World Bank (Washington, DC, 2014)
Diversifying Poland's financial system to meet new demands while preserving its resilience and stability is the key task ahead for financial policymakers. Over the past decade, the financial system has grown rapidly and risks have been well managed along the way. To maintain this track record and supply the financial services needed to support the economy's growth, it will be important to develop nonbank financial intermediation, prepare for possible further consolidation and exit of financial institutions, especially cooperatives, credit unions (SKOKs), and small banks, and promote a competitive banking system, relying less on foreign funding. While these developments will be largely market driven, they need to be supported by enabling regulatory reform and the modernization of the financial oversight framework: supervision focused on risk management, including an independent systemic risk perspective, strong safety nets, and state-of-the-art resolution tools will be indispensable. A joint IMF-World Bank mission visited Poland from February 19 - March 6, 2013 to undertake an update of the Financial Sector Assessment Program (FSAP) conducted in 2006. This report summarizes the main findings of the mission, identifies key financial sector vulnerabilities, and provides policy recommendations.